Main tasks of implementation of international labor protection regulations in the legal field of Ukraine - Zdanovsky, Volodymyr G.; Glyva, Valentyn A.; Burdeina, Nataiia B. (Kyiv National University of Construction and Architecture, 2022)
The paper analyzes the legislative regulation in the field of labor protection in Ukraine and identifies the main directions of work to improve it. In connection with Ukraine’s move towards EU membership, it is advisable to focus on EU regulations. It is shown that such acts are both general in nature and consider certain aspects of labor protection (certain factors of harmful effects). The advantage of the European directives on occupational safety is that they contain mandatory annexes that quantify the permissible harmful effects. The joint work of experts of the EU and the International Labor Organization on the draft Law of Ukraine on labor protection is analyzed. Due to a number of shortcomings, these materials are generally in line with the international level and require minimal harmonization with current national regulations. The advantage of the Project is a clear modern definition of "employee" and "employer". The same applies to the definition of the rights and responsibilities of employees and employers. For the first time in Ukraine, a risk-based approach to possible dangers for workers has been recognized at the legislative level. It is advisable to detail its requirements in bylaws for certain industries, taking into account the significant achievements of domestic scientists. This need is due to the lack of clearly defined methods of calculating occupational risks. The advantage of the Project is also targeted regulation of penalties for non-compliance with the Law. The implementation of the law, with some modifications, will contribute to the safety and health of workers.